The Canonical Relationship between the School Administrator’s Academic Management and the Teacher’s Happiness at Work in Sura Nari Witthaya School, Nakhon Ratchasima Province - Rodkaew, Chatchai; Deepu, Sanrudee (Ratchaphruek Journal, 2021)
The research objectives were to study 1) the school administrator’s academic management and the teacher’s happiness at work, and 2) the canonical correlation between the school administrator’s academic management and the teacher’s happiness at work. The samples were 144 teachers in Sura Nari Witthaya School, Nakhon Ratchasima province who were selected by using simple random sampling. Research instruments were questionnaires on the school administrator’s academic management questionnaire, and the teacher’s happiness at work. The data were analyzed by mean, standard deviation, and canonical correlation. The research results were 1) the school administrator’s academic management was at a highest level, and the teacher’s happiness at work was at a high level, and2) the canonical correlation between the set of variables on the school administrator’s academic management and the teacher’s happiness at work had one function with statistical significance at the .01 levels,canonical correlation coefficient was at .506 and covariance was at 25.600. Also, the set of variables on the school administrator’s academic management with the weight affecting canonical variables (U1) of curriculum administration, instruction management, measurement and evaluation, and educational supervision were at -.936, -.913, -.735, and -.725, respectively, plus the set of variables on the teacher’s happiness at work with the weight affecting canonical variables (V1) of connection, work achievement, love of work, and recognition at -.859, -.762, -.471, and -.427, respectively.